Evaluating heterogeneity in ASD symptomatology, cognitive ability, and adaptive functioning among 16p11.2 CNV carriers. Issue 8 (28th June 2020) - Hudac, Caitlin M.; Bove, Joanna; Barber, Shelley; Duyzend, Michael; Wallace, Ari; Martin, Christa Lese; Ledbetter, David H.; Hanson, Ellen; Goin‐Kochel, Robin P.; Green‐Snyder, LeeAnne; Chung, Wendy K.; Eichler, Evan E.; et al.
Abstract : Individuals with 16p11.2 copy number variant (CNV) show considerable phenotypic heterogeneity. Although autism spectrum disorder (ASD) is reported in approximately 20–23% of individuals with 16p11.2 CNVs, ASD‐associated symptoms are observed in those without a clinical ASD diagnosis. Previous work has shown that genetic variation and prenatal and perinatal birth complications influence ASD risk and symptom severity. This study examined the impact of genetic and environmental risk factors on phenotypic heterogeneity among 16p11.2 CNV carriers. Participants included individuals with a 16p11.2 deletion ( N = 96) or duplication ( N = 77) with exome sequencing from the Simons VIP study. The presence of prenatal factors, perinatal events, additional genetic events, and gender was studied. Regression analyses examined the contribution of each risk factor on ASD symptomatology, cognitive functioning, and adaptive abilities. For deletion carriers, perinatal and additional genetic events were associated with increased ASD symptomatology and decrements in cognitive and adaptive functioning. For duplication carriers, secondary genetic events were associated with greater cognitive impairments. Being female sex was a protective factor for both deletion and duplication carriers. Our findings suggest that ASD‐associated risk factors contribute to the variability in symptom presentation in individuals with 16p11.2 CNVs. Lay Summary: There are a wide range of autism spectrum disorder (ASD) symptoms and abilities observed for individuals with genetic changes of the 16p11.2 region. Here, we found perinatal complications contributed to more severe ASD symptoms (deletion carriers) and additional genetic mutations contributed to decreased cognitive abilities (deletion and duplication carriers). A potential protective factor was also observed for females with 16p11.2 variations. Autism Res 2020, 13: 1300–1310 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.